A study on the adoption of BIM to increase FM productivity in Kuala Lumpur - Malikzay, Mohammad Nasim (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
The demand of building information modeling has been increased lately as much international associations and governments taking the initiative to encourage BIM in building life-cycle. Although the putting into practice of BIM is not an easy task, BIM is capable to benefits and well-organize information management in facilities management. There will be the progress of the quality of life in the place of work when accepting BIM in FM that includes multiple discipline to guarantee higher functionality of the built environment by incorporating technology, process, place and people. Therefore, this research is conducted as to identify how to integrate FM information in BIM, to determine the adoption of BIM in FM Industry, to identify the challenges and barriers in practicing Building Information Modelling for Facilities Management and to determine how to improve FM productivity by using building information modelling. The method of research used is quantitative analysis with the application of questionnaire survey as technique of data collection. From the method carried out 50 respondents consist of managers, contractors, officers, directors, team leaders and students have provided the feedback and the results obtained are analyzed using Statistical Social Package Science and are simplified using Microsoft word. For the first objective, the integration of FM in formation in BIM include involving FM in the process is the key to ensure the availability of the proper dataset of information, supporting the idea of a BIM-based knowledge management system and currently the major issues that affect the integration of FM information in BIM are: “as built” hard copy, updated building documentation, inconsistency of the information, no inventory of building assets and components and no documentation about the building envelope. While for the second objectives, the adoption of BIM in FM include use the implementation output as input to strategic decision-making and for the third objective, the challenges and barriers of adopting BIM in FM include lack of training. BIM is principally a tool for design and construction. For the last objective, to improve FM productivity include identify errors early, strong influence on project duration and reduce rework.